THU0310 CASE–CONTROL SEROPREVALENCE STUDY ON THE ASSOCIATION BETWEEN BARTONELLA INFECTION AND ANTI-NEUTROPHIL CYTOPLASMIC ANTIBODY-ASSOCIATED VASCULITIS. (2nd June 2020) - Mahr, A.; Edouard, S.; Cornec, D.; Gonzalez-Chiappe, S.; Goronzy, J.; Guilpain, P.; Langford, C.; Lévy, P. Y.; Merkel, P. A.; Monach, P.; St Clair, E. W.; Seo, P.; et al.
Abstract : Background: Bartonellosis is an emerging anthropozoonosis caused by infection with intracellular Gram-negative Bartonella species. It leads to necrotizing granulomas and endothelial damage and causes acute and chronic human diseases, such as cat scratch disease, bacillary angiomatosis and endocarditis. Endocarditis due to Bartonella henselae and B. quintana is reported to produce anti-neutrophil cytoplasmic antibodies (ANCAs) that disappear with effective antimicrobial treatment. Objectives: Hypothesizing a role for Bartonella infection in ANCA-associated vasculitis (AAV), which also includes granulomatous and vascular inflammation, we studied the seroprevalence of 5 Bartonella species in patients with AAV. Methods: The study used plasma samples from patients with granulomatosis with polyangiitis and microscopic polyangiitis that were enrolled in the Rituximab for AAV (RAVE) trial and from healthy controls living in the United States. Western blot assays were used for serological testing of infection with B. quintana, B. henselae Houston-1, B. elizabethae, B. vinsonii subsp. berkhoffii and B. alsatica . The associations of positive serology results and AAV were expressed as odds ratios (OR). Clinical characteristics of seropositive and seronegative patients, assessed by the BVAS/WG instrument, were compared. These comparisons were done for 9 organ systems; in case they showed differences with P <0.10, the corresponding organ system-specific clinical features were also analyzed. Statistical analysis was performed using Fisher's exact test or Student's t-test, as appropriate. Results: We analyzed blood samples of 187 patients with AAV (collected at start of the trial) and of 127 controls. There were no significant differences between the cases and controls for mean age ( P =0.148) and proportion of males ( P =0.36). Bartonella spp. serological testing was positive for 112 (60%) cases and 40 (31%) controls (OR 3.25 [95% CI 2.02–5.22], P <0.001). Significant associations were also found within subsets of PR3-AAV (OR 4.00 [95% CI 2.37–6.76], P <0.001), MPO-AAV (OR 2.18 [95% CI 1.17–4.06], P= 0.017), newly-diagnosed (OR 3.89 [95% CI 2.21–6.86], P <0.001) and relapsing disease (OR 2.86 [95% CI 1.65–4.98], P <0.001). Species-specific positive serological testing was found in particular against B. henselae (cases: 27%, controls: 0.8%; OR 39.93 [95% CI 5.42–293.90]; P <0.001). Compared to AAV patients without seropositivity for Bartonella spp., AAV patients testing seropositive for Bartonella spp. had significantly more bloody nasal discharge ( P =0.046), sinus involvement ( P =0.035) and conjunctivitis/episcleritis ( P =0.016). Conclusion: This study reveals higher seroprevalence of Bartonella, especially B. henselae, in patients with AAV than in healthy controls. Although cross-reactivity of Bartonella with other microorganisms cannot be excluded, these results may support an etiopathogenic role of Bartonella infection in AAV that deserves further investigation. Disclosure of Interests: Alfred Mahr Consultant of: Celgene, Speakers bureau: Roche, Chugai, Sophie Edouard: None declared, Divi Cornec: None declared, Solange GONZALEZ-CHIAPPE: None declared, Jörg Goronzy: None declared, Philippe Guilpain: None declared, Carol Langford: None declared, Pierre-Yves Lévy: None declared, Peter A. Merkel: None declared, Paul Monach: None declared, E. William St. Clair: None declared, Philip Seo: None declared, Robert Spiera Grant/research support from: Roche-Genetech, GSK, Boehringer Ingelheim, Chemocentryx, Corbus, Forbius, Sanofi, Inflarx, Consultant of: Roche-Genetech, GSK, CSL Behring, Sanofi, Janssen, Chemocentryx, Forbius, Mistubishi Tanabe, Cornelia Weyand: None declared, John H. Stone Grant/research support from: Roche, Consultant of: Roche, Didier Rauolt: None declared, Ulrich Specks: None declared